1991
DOI: 10.1159/000235527
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Development of Lung Inflammation and Changes in Bone Marrow Populations in Guinea-Pigs following Inhaled Antigen Challenge

Abstract: Sensitised guinea-pigs were exposed to aerosolised antigen. The resultant cellular infiltration into the lung was assessed in lung tissue and bronchoalveolar lavage fluid 6, 24, 72 h and 7 days later. An early neutrophil infiltration peaking at 6 h was succeeded by eosinophil migration which persisted for 7 days, at which time some of the eosinophils appeared immature. The lung eosinophilia was accompanied by an initial fall in eosinophilic cells in the bone marrow, followed by an increase in this population. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…The present study went further in demonstrating the CD4+ nature of the T cells infiltrating the bronchial mucosa, by using the monoclo nal antibody H155. Other recent studies, using the same antibodies, showed that T cells increased in the BAL fluid after antigen challenge in immunized guinea pigs, but found no increase in the CD4+ population [13]. In conclusion, the expansion of the CD4+ population and eosinophils showed here in correlation with the devel opment of BHR previously demonstrated in this model opens new possibilities for the investigation of the immunopathogenesis of asthma and associated conditions and of its pharmacological modulation.…”
Section: Discussionsupporting
confidence: 75%
“…The present study went further in demonstrating the CD4+ nature of the T cells infiltrating the bronchial mucosa, by using the monoclo nal antibody H155. Other recent studies, using the same antibodies, showed that T cells increased in the BAL fluid after antigen challenge in immunized guinea pigs, but found no increase in the CD4+ population [13]. In conclusion, the expansion of the CD4+ population and eosinophils showed here in correlation with the devel opment of BHR previously demonstrated in this model opens new possibilities for the investigation of the immunopathogenesis of asthma and associated conditions and of its pharmacological modulation.…”
Section: Discussionsupporting
confidence: 75%
“…Glucocorticoids are widely used for the treatment of allergic disorders (Schleimer, 1990; Barnes, 1995), and indeed dexamethasone (Dex) is routinely used to characterize in vivo models of allergic inflammation. For instance, administration of this steroid to guinea‐pigs or rats profoundly affected the infiltration of eosinophils into the trachea following allergen challenge (Barton et al , 1991; Elwood et al , 1992). In addition, Dex prevented eosinophil accumulation in tissue sites other than within the respiratory tract such as the mouse peritoneal cavity or rat pleural cavity (Spicer et al , 1986; Zuany‐Amorim et al , 1993; Bozza et al , 1993).…”
Section: Introductionmentioning
confidence: 99%
“…A s has been found in guinea pigs by others [12,13], O A sensitisation followed by aerosol challenge led to pro nounced increases in the number and percent of eosino phils in their B A L fluids. However, there were significant differences between eosinophil numbers in parasite-naive guinea pigs with genetically determined differences in their responsiveness to the nematode parasite T. colubriformis.…”
Section: Discussionmentioning
confidence: 73%